Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - 2.7 - Inverse Functions - 2.7 Exercises - Page 228: 15



Work Step by Step

Show that f(g(x))=g(f(x)=x. f(g(x))=f(4x+9)=(4x+9-9)/4=4x/4=x g(f(x))=g($\frac{x-9}{4}$)=4($\frac{x-9}{4}$)+9=x-9+9=x
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.